Implementasi kebijakan usaha pakan untuk mendukung pengembangan industri perunggasan - Shaffitri, Lidya Rahma; Wahida; Perdana, Resty Puspa; Ilham, Nyak; Suryana, Esty Asriyana (Analisis Kebijakan Pertanian, 2024)
The primary raw material for broiler chicken feed is corn. Until now, most of the corn used for animal feed comes from imports. Policies to support the use of local feed raw materials other than corn and soybeans at reasonable prices are essential to increase the competitiveness of the broiler meat business. The policy prohibiting antibiotic growth promoters (AGP) in feed has not been widely followed due to farmers' concerns that it will have an impact on reducing the performance of broiler chickens. This study aims to identify regulations related to the development of the broiler feed industry and evaluate their implementation. The scope of the study is national, with data collection carried out specifically in the provinces of West Java, West Sumatra, and South Sulawesi in 2022. Data was collected by interviews with key informants and focus group discussions. Data analysis was carried out descriptively based on the modified OECD policy-cycle framework. To promote the efficiency of the national broiler chicken industry, a policy of developing local feed ingredients as a source of energy and protein with sufficient quality and quantity at competitive prices is needed. The prohibition on using AGP should be followed by supervision and encouraging mass production of AGP substitutes from herbal raw materials.